Impact of ovarian metastases on survival in patients treated with cytoreductive surgery and hyperthermic intraperitoneal chemotherapy for peritoneal malignancy originating from appendiceal and colorectal cancer. (2nd August 2018) - Bignell, M. B.; Mehta, A. M.; Alves, S.; Chandrakumaran, K.; Dayal, S. P.; Mohamed, F.; Cecil, T. D.; Moran, B. J.
Abstract: Aim: Ovarian metastases from gastrointestinal tract malignancies have been considered an ominous finding with poor prognosis. The aim of this project was to determine the impact on survival, and potential cure, when cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) are combined to treat peritoneal malignancy in women with Krukenberg tumours. Method: A retrospective analysis of prospectively collected data between January 2010 and July 2015. Female patients undergoing complete CRS (macroscopic tumour removal) and HIPEC for pseudomyxoma peritonei (PMP) of appendiceal origin, or colorectal peritoneal metastases (CPM) were included. Survival was estimated using the Kaplan–Meier method and survival rates compared using the log‐rank test. Results: In total, 889 patients underwent surgery for peritoneal malignancy, of whom 551 were female. Of these, 504/551 (91%) underwent complete CRS and HIPEC. Overall, 405/504 (80%) had at least one involved ovary removed either during CRS and HIPEC or at their index prereferral operation. Three hundred and fifty‐two patients (87%) had an appendiceal tumour and 53 (13%) had CPM. At a median follow up of 40 months, overall survival (OS) did not differ significantly between patients with or without ovarian involvement in women with a primary low‐grade appendiceal tumour or CPM. In women with high‐grade primary appendiceal pathology, OS was significantly lower in patients with ovarian metastases compared with those without ovarian involvement. Conclusion: Women with ovarian metastases from low‐grade appendiceal tumours or colorectal cancer treated with CRS and HIPEC have similar survival rates to patients without ovarian metastases. Long‐term survival and cure is feasible in patients amenable to complete tumour removal.